Warriors. Graystripe's adventure 1, The lost warrior - Hunter, Erin; Jolley, Dan (Hunter, Erin. Warriors., 2007)
When the Twolegs destroy the warrior Caln's forest home, Graystripe -- second in command of ThunderClan -- is captured trying to help his comrades escape! Trapped in the pampered life of a kittypet, Graystripe has all the food and shelter he needs from his affectionate Twoleg family, but this is not the way he wants to live. The forest is calling him, and he never stops longing to go home. When he makes friends with a feisty kittypet named Millie, she encourages him to go in search of his lost friends. But will Graystripe ever find his way back to the Clan?